2013
DOI: 10.1080/01973533.2013.823619
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Regulatory Focus on Responding to and Avoiding Slips in a Longitudinal Study of Smoking Cessation

Abstract: Promotion and prevention focus have been shown to uniquely predict the initiation and maintenance of behavior change, but the behavioral tasks underlying these effects have not been specified. We examined the effects of regulatory focus on how smokers responded to initial slips and whether smokers were able to avoid slips after initial cessation. After slipping, smokers higher versus lower in promotion focus were more likely to quit again, particularly if they were high in self-efficacy. Of participants quit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 33 publications
5
30
1
Order By: Relevance
“…Thus, promotion-focused people should be well suited to initiating changes that are focused on benefits, whereas prevention-focused people should be well suited to maintaining change as a means to preserve desired outcomes. Research in both the laboratory 22 and field 12,26 has supported these premises. Important to the present investigation, of successful losers (≥ 5% of initial weight), Fuglestad et al 12 found that promotion-focused people performed well if they were far from their goal weights (ie, still striving to attain desired outcomes), whereas prevention-focused people performed well if they were close to their goal weights (ie, vigilantly preserving desired outcomes).…”
Section: The Roles Of Regulatory Focus and Regulatory Fit In Weight Lmentioning
confidence: 84%
See 3 more Smart Citations
“…Thus, promotion-focused people should be well suited to initiating changes that are focused on benefits, whereas prevention-focused people should be well suited to maintaining change as a means to preserve desired outcomes. Research in both the laboratory 22 and field 12,26 has supported these premises. Important to the present investigation, of successful losers (≥ 5% of initial weight), Fuglestad et al 12 found that promotion-focused people performed well if they were far from their goal weights (ie, still striving to attain desired outcomes), whereas prevention-focused people performed well if they were close to their goal weights (ie, vigilantly preserving desired outcomes).…”
Section: The Roles Of Regulatory Focus and Regulatory Fit In Weight Lmentioning
confidence: 84%
“…Furthermore, conditions of non-fit (ie, when strategy by which an outcome is pursued does not match one’s psychological/motivational disposition) can result in poorer functioning. 26,31,32 It may be that the incongruence between the intervention strategy provided (a maintenance focus) and people’s readiness for maintenance (still far from weight loss goals) did not work well for people who were prevention-focused. Perhaps these people became overwhelmed by the onset of weight gain after having worked to achieve significant weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, promotion focus predicted higher initiation of both smoking cessation and weight loss, whereas prevention focus predicted higher maintenance over a year (Fuglestad et al, 2008). Similarly, it was found that after relapses, promotion‐focused smokers were more likely to quit smoking again, but were less likely to prevent future relapses after 2 months of smoking cessation (Fuglestad, Rothman, & Jeffery, 2013). Based on the above reasoning, it could be suggested that for the low active group of nurses, who still did not develop a habit, promotion focus helps initiating the process of habitual physical activity.…”
Section: Discussionmentioning
confidence: 99%